THE INFLUENCE OF KNOWLEDGE, ATTITUDE AND SELF EFFICACY ON THE PREPAREDNESS OF THE ELDERLY IN FACING DISASTER - Sitohang, Tiur Romatua (Universitas Aisyah Pringsewu, 2023)
In occurance of calamity, the elderly develop a particularly vulnerable populations. Handling to initiative catastrophe victims with properly and immediately will result in fewer casualties. Mitigating preparedness, particularly for the elderly, is one step used to lessen the effects of disasters. Many elderly people suffer because they are not well prepared to deal with disasters, such as by not having an emergency plan or appropriate knowledge of disasters. The main objective of this study is to determine the preparedness disaster of elderly in relation to their knowledge, attitudes, and self efficacy. This type of research was quantitative with a cross-sectional design. The research sample consisted of 280 people using random sampling techniques. The data was analized with linear regression t-test to determine the influence of knowledge, attitude, and self efficacy of elderly population readiness. The F-test is used to determine the simultaneous influence of knowledge, attitudes, and self-efficacy on the preparedness of the elderly in facing a natural catastrophe. The results show the characteristics of the majority of respondents were 153 women (54.6%), the majority were elderly aged 55-65 years as many as 180 people (64.2%) and the majority of elderly people lived with their partner (husband/wife). The results showed that attitude has no influence on disaster preparedness, the calculated t value t table (-1,351 1,667), self-efficacy has an influence on preparedness in facing disasters with t calculated t tabel (3,816 1,667), the knowledge variable has an influence on the preparedness of the elderly in facing disasters with t count t table (1,974 1,667). These results show that there is an influence of self-efficacy on elderly preparedness. Simultaneously knowledge, attitude, and self efficacy on the elderly preparedness in facing natural disasters with F cunt greater that F table value (6,512 1,65) and a significance value of 0,000